SHOULD STATINS BE DISCONTINUED IN PERI-OPERATIVE PERIOD? - V. V. Lomivorotov; S. M. Efremov; M. N. Abubakirov; D. N. Merekin (Вестник анестезиологии и реаниматологии)
HMG-CoA (3-hydroxy-3-methyl-glutaryl-coenzyme A) reductase inhibitors, which are more known as statins, reduce the level of low density lipoproteids and total cholesterol in blood plasma. Their efficiency for primary and secondary prevention of cardiovascular disorders has been proved by numerous trials. Additionally to the main mechanism of actions, statins possess pleiotropic properties, including anti-inflammatory endothelium protection, platelet stabilization, reduction of fibrinogen concentration and prevention of neurodegenerative and oncological disorders. Despite the vigilance of side effects, which has been growing of late, statins remain to be the drugs which are prescribed most often in the whole world. The article describes different strategies of statins use in the peri-operative period in the patients undergoing cardiac and general surgery.